Screw complication of ACL reconstruction: report of two cases - Che Ahmad, Aminudin; Ismail, Raffael; Zakaria@Mohamad, Zamzuri; Zulkifly, Ahmad Hafiz (2010)
Background: We analyzed the complication of ACL reconstruction of the knee which was done at Hospital Tengku Ampuan Afzan, Kuantan, Pahang from 2004 to 2008. Hundred and sixty three cases were operated. Complication arte were about 11% (18 patients) including revision surgery rate of 3.7% (6 patients). We are illustrating two cases of uncommon complication of screw that encounter in ACL surgical reconstructed patients. Case 1: 28 years old man undergo ACL reconstruction at 2004 using bone patella tendon bone (BPTB) graft and fixed with titatium screw. However the femoral screw was dislodging posterior and remains three for three years until he was consented for open removal of the screw. Post operatively uneventful. Case 2: 22 years old man presented in August 2009 with tibial screw protruding through the skin since a week prior to the consultation. The ACL reconstruction was done 2 years before (2007). Emergency removal of the screw and debridement revealed well fixed screw without loosening and no evidence of infection. Histopathological review and culture and sensitivity did not found any evidence of infection. The knee remains stable without any laxity. Conclusion: Using a screw for fixation of the graft in ACL reconstruction carefully and appropriately is mandatory to avoid the complication of both at the femoral and tibial components.